Vegetable soybean: seed composition and production research - Zhang, Qiuying; Li, Yansheng; Chin, Kit L.; Qi, Yadong (Italian Journal of Agronomy, 2017)
Vegetable soybean (edamame) [Glycine max (L.) Merr.] is a low input, high nutritional value, short crop cycle and soil-enriching profitable crop. It offers quick economic return and provides health benefits to the consumers. The market demand for edamame has begun to flourish and expand dramatically in recent decades due to increased awareness of nutritional properties, and the change in life styles towards healthier food. This article highlighted the importance of edamame as a nutraceutical and functional food-grade produce, summarised the research advances in seed composition and their roles, cultivar selection and crop establishment, planting date and fertilisation, weed management and harvesting. Current production problem of extensive labor at harvest and future research challenges in improving crop establishment, developing cultivars competitive to weed and resistant to pest insects/diseases, assessing biological activities of edamame elemental and phytochemical properties on cancer cell inhibition, and developing organic production system were also proposed with aims of enhancing farm profitability and expanding opportunities for extensive use of edamame.